Pause and Rewind: Memories of Age-Inappropriate Film Viewings in the 1980s - Turner, Peter (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
This article explores some of the findings from a work-in-progress project that I began working on in 2020 to investigate the retrospective memories of 1980s British audiences surrounding viewing films classified either 15 or 18 by the BBFC, while the participants were underage. I question the so-called victims of censorship that have matured into their 40s and are no longer at the mercy of parents or the classifications of the BBFC in order to investigate the retrospective memories of these adults who were once participating in forbidden viewings as children in the 1980s. This article explores Annette Kuhn’s idea that for audiences, the movie fades from memory to make way for more movies, but it is the life experiences that stay with the viewer. By focusing on underage viewers and films that had been deemed unsuitable for their age, I hope to review Kuhn’s claim, by resituating the film itself as the prominent memory – a memory not replaced by many decades of movie watching since. This article outlines the methodology for the project, before turning to a discussion of participants’ memories of interrupted film viewings. In exploring the dichotomy between memories of viewing conditions and memories of the film themselves, this article then considers memories of the horror genre (and terrifying scenes in other genres), and also the issues of watching sex in films, and the impact of parental restrictions, or watching while with parents.